Fatigue Life Estimation Models: A State of the Art - Kamal, M.; M. M., Rahman (Universiti Malaysia Pahang, 2014)
In this paper, a state of the art of recently proposed fatigue prediction models has been conducted. The modified Wöhler curve method (MWCM) with a critical plane model utilizing the maximum variance method (MVM), and an endurance function model utilizing a stress invariant are studied for fatigue life evaluation. The results are compared with experimental results as well as results from already established fatigue models using a fatigue life estimation tool. The study shows that new models have good accuracy that is approximately the same as for the established models, and are easy to apply in various conditions like multiaxial and variable amplitude loading conditions, which is a limitation of the older models. It is concluded that the newly formulated models are a promising development and should be studied in detail to make their application simpler with complex real-world problems.